2023
DOI: 10.4236/jss.2023.111022
|View full text |Cite
|
Sign up to set email alerts
|

The Misconception in Differentiated Instruction Practices: A Literature Review

Abstract: This paper aims to stimulate reflective discussion about the misconception of differentiated instruction practice in the educational sector. Differentiated instruction gives students a big picture of knowledge instead of isolated knowledge and helps students to find their academic goals. While differentiating, teachers as a facilitator have to implement and arrange a differentiated learning opportunity for students. This idea widens the gap between teachers' perception of how varied teaching should be used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Finally, the 'product' relied primarily on generating diverse projects based on the student's interests, level of readiness, and profiles, rather than traditional examinations. The results contrasted Putra (2023) whose findings revealed a misconception between adapting differentiated instruction and individualized learning. Adare, Li & Gebresilase (2023) also announced unsatisfactory teachers' competency to adapt to the environment which is considered a major component of adapting process.…”
Section: Table (1): Testing Normality For Implementation Of Different...mentioning
confidence: 56%
“…Finally, the 'product' relied primarily on generating diverse projects based on the student's interests, level of readiness, and profiles, rather than traditional examinations. The results contrasted Putra (2023) whose findings revealed a misconception between adapting differentiated instruction and individualized learning. Adare, Li & Gebresilase (2023) also announced unsatisfactory teachers' competency to adapt to the environment which is considered a major component of adapting process.…”
Section: Table (1): Testing Normality For Implementation Of Different...mentioning
confidence: 56%
“…The curriculums aspects that teachers need to consider in differentiated instruction are related to two main aspects: the components Putra (2023) explains that we need to overcome these barriers because teachers" misunderstandings pose a significant obstacle to implementing differentiated instruction in the classroom. Teachers" awareness of applying different learning approaches will influence students" learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, there are several challenges and obstacles in the implementation of the components of differentiated instruction. Putra (2023) explains that many studies have found misconceptions among training facilities and developing teachers" competencies in managing differentiated learning (Fitri et al, 2020;Muhith et al, 2023).…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiated instruction (DI) is an approach that enables teachers to plan strategically to meet the needs of every student. This concept is rooted in the concept that because there is variability among any group of learners, teachers should expect student diversity and adjust their instruction accordingly (Tomlinson, 2014;Tomlinson, 2017;Putra, 2023). Differentiated instruction focuses on a diversity-based approach (Tomlinson et al, 2003), which can help students meet their learning needs based on different aspects such as readiness, interests, and learning profiles (Tomlinson, 2014;Tomlinson, 2017;Du Plessis, 2019;Gheyssens et al, 2022).…”
Section: Introductionmentioning
confidence: 99%